Anxiety and motor performance: More evidence for the effectiveness of holistic process goals as a solution to the process goal paradox. (November 2016) - Mullen, Richard; Jones, Eleri Sian; Oliver, Samuel; Hardy, Lew
Abstract: Objectives: Recent research has reported the benefits of using holistic rather than part process goals to avoid the negative effects associated with the conscious processing of task relevant information by skilled but anxious athletes. This experiment compared the efficacy of these two goal focus strategies in a neutral condition and a competitive condition in which cognitive state anxiety was elevated. Design: Laboratory-based experimental design using a mixed model with between (process goal groups) and within-subjects (neutral and competitive) conditions. Method: Thirty male and female undergraduate students aged between 19 and 44 years of age completed 896 practice repetitions of a race car driving simulation using discovery learning. Participants were then placed in either a holistic or part process goal group using stratified random assignment. The practice phase was followed by neutral and competitive conditions, during which driving performance and psychophysiological measures were collected. Results: Analysis of variance of lap times and driving errors revealed that the holistic process goal group outperformed the part process goal group in the competition condition. Analysis of psychophysiological measures suggested that the performance of both process goal groups in the competitive condition was associated with the investment of compensatory effort. Conclusions: Compared to part process goals, holistic process goals confer performance benefits for skilled athletes who perform under competitive pressure. Highlights: Low frequency heart rate variability is reflective of compensatory mental effort. Holistic rather than part process goals are a more effective competition strategy. Salivary alpha amylase is a potential neuroendocrinological indicator of anxiety.